APLIKASI PENGAJUAN CUTI KARYAWAN BERBASIS ANDROID - Syam, Syahriani; Lestari, Sri (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
The world of work today requires technology coverage, especially in employee management, the employees themselves are very important for the company, without employees the company cannot run optimally. One of the employee management is on their leave rights. Currently, the employee leave application process still uses a manual form, for example, to find out the remaining leave & apply for leave, you must first request a leave form, fill in the date of leave and provide data on leave requirements. Therefore the researchers designed an Android-based leave application. The method used is UML (Unified Modeling Language), for programming using the Android Studio text editor, and the database using MySql Workbench. The current employee leave application can only be used in the Android Studio emulator. researchers produce application features for submitting employee leave that can meet the needs of employees. With the Employee Leave Submission Application, it can make leave applications more effective & efficient